Food Safety in Africa : Past Endeavors and Future Directions - World Bank (Washington, DC: World Bank, 2022)
Current donor investment in food safety in Sub-Saharan Africa (SSA) largely reflects the concerns of previous decades and as a result is substantially focused on access to regional and overseas export markets, with emphasis on national control systems. Relatively little is being done to reduce foodborne illness among consumers in SSA. More investment in food safety (by African governments, donors, and the private sector) is needed to help ensure that Africans have safe food. New understanding of foodborne disease burden and management, along with rapid and broad change within societies and agri-food systems in SSA, has led to food safety emerging as an important public health and development issue. There is need to reconsider donor and national government investment strategies and the role of the private sector. This report is a call for action on food safety. It provides up-to-date information on key food safety actors, presents the first-ever analysis of food safety investments in SSA, captures insights from a wide-ranging expert consultation and makes suggestions for attaining food safety, based on evidence but also consensus principles, successful elsewhere but not yet applied widely in mass domestic markets in SSA.